Constraining past accumulation in the central Pine Island Glacier basin, West Antarctica, using radio-echo sounding. Issue 221 (2014) - Karlsson, Nanna B.; Bingham, Robert G.; Rippin, David M.; Hindmarsh, Richard C.A.; Corr, Hugh F.J.; Vaughan, David G.
Abstract: The potential for future dynamical instability of Pine Island Glacier, West Antarctica, has been addressed in a number of studies, but information on its past remains limited. In this study we use airborne radio-echo sounding (RES) data acquired over Pine Island Glacier to investigate past variations in accumulation pattern. In the dataset a distinctive pattern of layers was identified in the central part of the glacier basin. We use these layers as chronological identifiers in order to construct elevation maps of the internal stratigraphy. The observed internal layer stratigraphy is then compared to calculated stratigraphy from a three-dimensional ice-flow model that has been forced with different accumulation scenarios. The model results indicate that the accumulation pattern is likely to have changed at least twice since the deposition of the deepest identified layer. Additional RES data linked to the Byrd ice core provide an approximate timescale. This timescale suggests that the layers were deposited at the beginning of or during the Holocene period. Thus the widespread changes occurring in the coastal extent of the West Antarctic ice sheet at the end of the last glacial period could have been accompanied by changes in accumulation pattern.